Avoiding mixed-methods? methodological and theoretical approaches in women’s radio participation research (2021)
Previous media studies that did meta-analyses of methodological and theoretical approaches have addressed subsets such as political communication, health communication, and gatekeeping. However, scant attention has been paid to women’s participation in radio discourse despite its importance to the developmental agenda. This study was, therefore, designed to investigate the methodological and theoretical trends in women’s radio participation studies. Content analysis was used to examine a total of 70 purposively selected women’s radio participation-related studies published between 2009 and 2019. Findings reveal that 55.7% of the analysed articles employed quantitative methodological approaches, while 25.7 % of the articles used qualitative approaches. Only 18.6% of the studies employed a mixed-methods design. Findings also show that more quantitative studies (67.5%) were hinged on theoretical frameworks compared to 32.5% not driven by theories. Conversely, fewer qualitative studies (27.8%) were driven by theories, while 72.2% were not theory-driven. Generally, 57.1% of the articles analysed had theoretical backgrounds. The pattern established in this study shows that existing women’s radio participation studies scantly adopted mixed-methods approaches, but the use of relevant theories as frameworks is fairly high. Scholars in the field of women’s radio participation research should adopt the mixed methods design as this would help in getting more robust and in-depth findings.